2021
DOI: 10.3390/ijms22158273
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of the pH Dependence of Stability of Melanosome Proteins: Implication for Melanosome formation and Disease

Abstract: Intravesicular pH plays a crucial role in melanosome maturation and function. Melanosomal pH changes during maturation from very acidic in the early stages to neutral in late stages. Neutral pH is critical for providing optimal conditions for the rate-limiting, pH-sensitive melanin-synthesizing enzyme tyrosinase (TYR). This dramatic change in pH is thought to result from the activity of several proteins that control melanosomal pH. Here, we computationally investigated the pH-dependent stability of several mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…Thus, a recent work computationally studied the pH-dependent stability of several melanosome membrane proteins. The authors found that disease-causing variants impact the pH-dependence of melanosome proteins [ 8 ]. Substitution of wild-type His with Gln was found to alter the function of CLIC2 protein and to cause X-linked channelopathy with cardiomegaly [ 108 ].…”
Section: Electrostatics and Disease Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a recent work computationally studied the pH-dependent stability of several melanosome membrane proteins. The authors found that disease-causing variants impact the pH-dependence of melanosome proteins [ 8 ]. Substitution of wild-type His with Gln was found to alter the function of CLIC2 protein and to cause X-linked channelopathy with cardiomegaly [ 108 ].…”
Section: Electrostatics and Disease Mechanismsmentioning
confidence: 99%
“…( b ) Mutation of D196G (SARS-CoV-2 spike protein) caused the loss of the hydrogen bond between THR and ASP (PDB: 7KMS [ 100 ]). ( c ) The pH-dependence of folding free energy for the melanosome of oculocutaneous albinism-2 [ 8 ]. ( d ) The image shows p53 protein–DNA and 1-[2-(1,3-benzodioxol-5-yl) pyrazolo[1,5-a] pyrazin-4-yl]-3-piperidinamine.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation